Malaria eradication in the Americas: A replication study of Bleakley (American Economic Journal. Applied Economics, 2010) - David Roodman (International Journal for Re-Views in Empirical Economics (IREE), 2018)
Bleakley (2010) finds that large-scale campaigns in the 20th century to eradicate malaria were followed by income gains for those native to historically endemic areas. I perform a pre-registered reanalysis and find these results to be largely robust. Malaria eradication efforts indeed appear to have been followed by anomalous income gains for natives of historically malarial areas of Brazil, Colombia, Mexico, and perhaps the United States. This supportive finding diverges from that of a separate, parallel reanalysis of Bleakley (2007), a study that finds long-term benefits from a hookworm eradication campaign in the United States
Keywords: I18; O15; 330; malaria; public health and economic development; replication study